Research on the Tip Clearance Measuring Method Based on AC Discharge - Bing Yu; Tao Zhang; Hongwei Ke; Tianhong Zhang (IEEE Access, 2020)
A new measuring system for the engine tip clearance based on alternate current discharge is proposed in this article. Firstly, theoretical analysis and numerical simulation of the system, as well as the experiment of gas discharge are introduced to prove the feasibility of the method. Then a validation platform is built to study the effects of different probe materials and structures, as well as changes in temperature and humidity under atmospheric pressure on the system. Finally, the system calibration and tip clearance measurement are carried out. The results show that tungsten copper probe with planar structure is more suitable for measuring the tip clearance. When the tip clearance is between 0-6mm, the designed system has high measurement accuracy and its measurement error within 0.05mm. Compared with the traditional spark discharge method, the proposed method not only has the similar advantages, but also overcomes many defects, and has a broader application prospect.